Curing Ingredients, Characteristics, Total Phenolic, and Antioxidant Activity of Commercial Indonesian Dried Meat Product (Dendeng) - T Suryati; M Astawan; H N Lioe; T Wresdiyati (Faculty of Animal Science, Bogor Agricultural University, 2012)
Dendeng is Indonesian dried meat product that used spices rich in antioxidant component as ingredient. In addition, commercial dendeng usually use saltpeter (nitrate/nitrite salt) as curing ingredient to inhibit rancidity and to produce stable red color. The aims of this study were to investigate composition of spices and saltpeter added, characteristic, total phenolic, and antioxidant activity of commercial dendeng. This research was conducted through interview with some dendeng producers to get information about saltpeter adding and spices composition used in their products. Then the interview results were verified by laboratory analysis. The results showed that spices and saltpeter adding from some producers varied. The saltpeter added in curing process produced inconsistent red color on commercial dendeng in this investigation. Total phenolic of dendeng from producers ranged from 42.47 to 102.0 mg GAE/100 g DM for raw dendeng, and 36.51 to 95.49 mg GAE/100 g DM for fried dendeng. Antioxidant capacity against DPPH ranged from 79.35 to 379.40 mg VCE/100 g DM for raw dendeng, and 94.30 to 559.40 mg VCE/100 g DM for fried dendeng. Antioxidant capacity of raw dendeng was influenced by phenolic content about 87.2%, but in fried dendeng was only 59.0%. In conclusion, dendeng has a significant antioxidant activity, even after frying, and saltpeter addition was not effective to maintain stable red color in dendeng products.